"From Myanmar to Malaysia": Examining the strategies by NGOs for livelihood of Rohingya / Kamarul Aini Hassan ...[et al.] - Hassan, Kamarul Aini; Mohd Arshad, Mohd Ramlan; Ajis, Mohd Na'eim; Khairi, Aizat (Universiti Teknologi MARA Cawangan Pahang, 2021)
Malaysia is a popular destination country among the Rohingya refugees but few studies have been conducted to examine the strategies of NGOs established by Rohingya to assist their own communities during their migration and integration in Malaysia. As Malaysia is not signatory to Refugee Convention 1951 and Protocol 1967, Rohingya refugees faced issues of limited access to health, formal education and safety protection. To fill this gap, a qualitative research with in-depth interview was employed on NGOs set up by Rohingyas refugees. Findings indicated that the Rohingya's NGOs played vital roles to help their own communities. It is recommended that policy-makers should ensure the proper implementation of refugee policy and align them with the international standard of practice in managing Rohingya refugees in Malaysia. The involvement of NGOs should be considered by Malaysian government in order to eliminate the negative view of citizens on the migration and integration of Rohingya refugees from Myanmar to Malaysia.